2019
DOI: 10.1017/s0144686x19001119
|View full text |Cite
|
Sign up to set email alerts
|

Carers’ experiences of timely access to and use of dementia care services in eight European countries

Abstract: Timely access to care services is crucial to support people with dementia and their family carers to live well. Carers of people with dementia (N = 390), recruited from eight countries, completed semi-structured interviews about their experiences of either accessing or not using formal care services over a 12-month period in the Access to Timely Formal Care (Actifcare) study. Participant responses were summarised using content analysis, categorised into clusters and frequencies were calculated. Less than half … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…A qualitative study explored the perspective of family caregivers, and their beliefs and motivations to use respite services, and found that the safety of the care recipient was a primary reason to use services, but only in case of functional deficits [ 42 ]. Similarly, a cross-cultural study reported that reasons for using support services included worsening in the condition of the person with dementia and the services’ ability to meet his needs [ 43 ]. Our results confirm that support conveys respite and relief to caregivers, but also suggest that caregivers may only reluctantly admit seeking help for themselves rather than for the person they care for [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study explored the perspective of family caregivers, and their beliefs and motivations to use respite services, and found that the safety of the care recipient was a primary reason to use services, but only in case of functional deficits [ 42 ]. Similarly, a cross-cultural study reported that reasons for using support services included worsening in the condition of the person with dementia and the services’ ability to meet his needs [ 43 ]. Our results confirm that support conveys respite and relief to caregivers, but also suggest that caregivers may only reluctantly admit seeking help for themselves rather than for the person they care for [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data reported on penetration often indicates access to the service in multiple ways, which seems to match the preferences and capabilities of consumers. As reported by Jelly et al [85], caregivers use dementia support services primarily when services are able to meet consumers' individual needs. However, it is important to keep in mind that, from an organizational point of view, these extended access options need to be served simultaneously.…”
Section: Principal Findingsmentioning
confidence: 97%